1983
DOI: 10.1111/j.1467-8624.1983.tb00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Later Competence and Adaptation in Infants Who Survive Severe Heart Defects

Abstract: A model of risk potential for developmental outcome was created based on cardiac, medical, surgical, and family-stress factors in 31 children with transposition of the great arteries who had undergone reparative open heart surgery utilizing cardiopulmonary bypass during infancy. Impact of these potential risk factors was assessed by 4 current neurologic measures (neurologic anatomic abnormalities, functional impairment, electroencephalograph [EEG], and Pattern Visual Evoked Potential [PVEP]) and 4 psychologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…In view of our results (deep hypothermic circulatory arrest appeared to be a predictor of long-term behavioural/emotional problems), we agree with the conclusion of Oates et al However, care should be taken when drawing firm conclusions since in our study the duration of deep hypothermic circulatory arrest and rate of cooling were not documented in a reliable manner. Several investigators have reported on the psychosocial sequelae of risk factors such as duration of pregnancy, hypoxia and age at surgical repair [1,5,7,18,19] . In a longitudinal study Weisglas-Kuperus et al [18] found that parents of very low birth weight children with a gestational age <36 weeks reported significantly more CBCL-Internalizing problems when their children were 3·5 years of age, than parents of a comparison group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In view of our results (deep hypothermic circulatory arrest appeared to be a predictor of long-term behavioural/emotional problems), we agree with the conclusion of Oates et al However, care should be taken when drawing firm conclusions since in our study the duration of deep hypothermic circulatory arrest and rate of cooling were not documented in a reliable manner. Several investigators have reported on the psychosocial sequelae of risk factors such as duration of pregnancy, hypoxia and age at surgical repair [1,5,7,18,19] . In a longitudinal study Weisglas-Kuperus et al [18] found that parents of very low birth weight children with a gestational age <36 weeks reported significantly more CBCL-Internalizing problems when their children were 3·5 years of age, than parents of a comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study Weisglas-Kuperus et al [18] found that parents of very low birth weight children with a gestational age <36 weeks reported significantly more CBCL-Internalizing problems when their children were 3·5 years of age, than parents of a comparison group. O'Dougherty et al [5] found that prolonged hypoxia was one of several medical risk variables significantly associated with adverse psychosocial outcome in patients with transposition of the great arteries. In contrast, Oates et al [7] recently found no adverse effect from prolonged hypoxia on the intellectual development of 81 children who had cyanotic heart disease (transposition of the great arteries and tetralogy of Fallot).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In children with CHD, long-term studies using standardized tests of academic achievement have demonstrated lower scores compared with the controls [54]. Multiple risk factors such as chronic hypoxia, anesthesia, and potentially low cerebral blood flow during cardiopulmonary bypass may be responsible for these learning disabilities [35][36][37].…”
Section: Introductionmentioning
confidence: 99%